1994
DOI: 10.1038/ki.1994.129
|View full text |Cite
|
Sign up to set email alerts
|

Factors in the development of secondary hyperparathyroidism during graded renal failure in the rat

Abstract: Secondary hyperparathyroidism (2 degree HPT) develops as a result of renal failure. Hypocalcemia, phosphorus retention, calcitriol deficiency and skeletal resistance to the calcemic action of parathyroid hormone (PTH) are closely interrelated pathogenic factors important for the development of 2 degrees HPT in renal failure. Since previous studies have mainly focused on advanced renal failure, only limited data are available in early renal failure. The goal of the present study was to evaluate how alterations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 37 publications
3
32
0
1
Order By: Relevance
“…Dietary phosphate and vitamin D status are known to affect the development of hyperparathyroidism in both the normal and the azotemic state. Studies in normal and azotemic rats have shown that high dietary phosphate greatly increases PTH values (15,40). Conversely, dietary phosphate restriction reduces PTH values in normal rats and minimizes increases in PTH values in azotemic rats (13,41).…”
Section: Basal Pthmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary phosphate and vitamin D status are known to affect the development of hyperparathyroidism in both the normal and the azotemic state. Studies in normal and azotemic rats have shown that high dietary phosphate greatly increases PTH values (15,40). Conversely, dietary phosphate restriction reduces PTH values in normal rats and minimizes increases in PTH values in azotemic rats (13,41).…”
Section: Basal Pthmentioning
confidence: 99%
“…Phosphorus restriction and an increased serum calcitriol shift the EOP to the left (12)(13)(14) because less PTH is needed to maintain the same serum calcium concentration. Conversely, phosphorus loading, a deficiency of calcitriol, and renal failure shift the EOP to the right (15)(16)(17)(18)(19) because more PTH is needed to maintain the same serum calcium concentration.…”
Section: Bifunctional Relationship Between Pth and Serum Calciummentioning
confidence: 99%
“…In humans, it has been observed that although the overall urinary excretion of calcium is generally reduced, the fractional excretion of calcium (FECa) increases in advanced renal failure [4] but it does not happen the same in moderate renal failure [22]. The findings reported in animals [2,20] have not been able to clarify this matter. For this reason, further studies are needed to throw light on the pathogenesis of hyperparathyroidism subsequent to renal failure.…”
Section: Introductionmentioning
confidence: 48%
“…At first glance, this seems to be in disagreement with existing literature data. Indeed, in the study of Bover et al [26] of rats with only a mild degree of renal failure (serum creatinine 0.75-1 mg/dL) receiving a diet with comparable phosphorus content (0.6% P; 0.6% Ca), PTH levels almost doubled after 20 days of uremia. The reason for this discrepancy may be due to a difference in biological availability of the phosphorus in their diet versus that in the present study.…”
Section: Tablementioning
confidence: 99%
“…The good bioavailability of phosphorus in this diet is evidenced by the fact that animals receiving this food had distinctly higher urinary phosphorus concentrations compared to the rats receiving the STD. Although a high phosphorus diet has previously been used for the induction of secondary hyperparathyroidism in renal failure rats, [26] this is the first study in which bone histological parameters in animals fed a diet with low vs. high bioavailable phosphorus are compared. The development of sHPTH after phosphorus-loading may be attributed to the cumulative effect of various factors:…”
Section: Tablementioning
confidence: 99%